The Impact of the COVID-19 Pandemic on Examination of Pregnant Women (Antenatal Care): A Literature Review - Siti Roudhotul Jannah; Aini Ahmad (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2022)
COVID-19 pandemic is making universal, radical, and very rapid changes in the health services of many countries around the world, especially obstetrics. The World Health Organization states that Coronavirus Disease 2019 (Covid-19) is a global pandemic. As one of the vulnerable groups, pregnant women need to avoid Covid-19 transmission and maintain their health in the pandemic period. The purpose of the study was to look at some of the research together and gain a frame of mind in solving problems about antenatal care in the time of the covid-19 pandemic. Research methods using literature review studies are obtained through the database of international journal providers Proquest and Jurnal Scientific Indonesia through google scholar with keywords according to MESH (Medical Subject Heading) namely